2019
DOI: 10.3390/ma12081313
|View full text |Cite
|
Sign up to set email alerts
|

Permeability versus Design in TPMS Scaffolds

Abstract: Scaffolds for bone tissue engineering are porous structures that serve as support for cellular growth and, therefore, new tissue formation. The present work assessed the influence of the porous architecture of triply periodic minimal surface (TPMS) scaffolds on their macroscopic permeability behavior, combining numerical and experimental methods. The TPMS scaffolds considered were Schwartz D, Schwartz P, and Gyroid, which have been previously studied for bone tissue engineering, with 70% porosity. On the exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(42 citation statements)
references
References 19 publications
1
35
0
Order By: Relevance
“…Investigating 70% porous Schwarz and Gyroid produced using a photocurable polymer resin, they showed a dependency of permeability with the flow rate applied, which decreased inversely, and may explain the different values obtained in the present work. 17 Zhang et al also reported similar permeability values for graded porosities based on diamond geometries. 49 TPMS have gained scientific attention thanks to their outstanding mechanical properties despite their porous structure.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Investigating 70% porous Schwarz and Gyroid produced using a photocurable polymer resin, they showed a dependency of permeability with the flow rate applied, which decreased inversely, and may explain the different values obtained in the present work. 17 Zhang et al also reported similar permeability values for graded porosities based on diamond geometries. 49 TPMS have gained scientific attention thanks to their outstanding mechanical properties despite their porous structure.…”
Section: Discussionmentioning
confidence: 71%
“…14 Some researchers have also applied TPMS designs using polymers, mainly based on acrylates, polyamides or styrenes through stereolitography (SLA), to investigate the mass transport or mechanical properties of the structures. [15][16][17][18] While the above polymer-or metallic-based TPMS structures might show biocompatibility, few studies have exploited the use of resorbable polymers which can serve as temporary constructs and further integrate into the bone remodelling process. In the present work, polylactic acid (PLA) was investigated as substrate material to manufacture TPMS scaffolds through fused deposition modelling (FDM).…”
Section: Introductionmentioning
confidence: 99%
“…It could be seen in the results that the D surface had the highest specific surface (Guo et al, 2019). At the same time, many pieces of research indicated that the G surface had the highest permeability, which means adequate oxygen and nutrition delivery (Montazerian et al, 2017(Montazerian et al, , 2019Yang et al, 2018;Castro et al, 2019a;Ali et al, 2020). Therefore, the D and G surface might have the best bone growth, which needs to be verified by future biological experiments.…”
Section: Tpmsmentioning
confidence: 95%
“…We consider tissue growth simulations on more complex surfaces such as triply periodic minimal surface (TPMS) which has interconnected pores and high porosity to ensure cell penetration, vascular ingrowth, nutrient diffusion, and waste product elimination [29]. TPMSs are widely used for the scaffold model structure, especially in tissue engineering applications.…”
Section: Simulation Of Tissue Growth On Scaffold In 3dmentioning
confidence: 99%
“…TPMSs are widely used for the scaffold model structure, especially in tissue engineering applications. Castro et al [29] investigated the effect of the porous structure of TPMS scaffolds on the macroscopic permeability behavior using numerical and experimental methods. The scaffold regions for the P, D, and G surfaces are defined by…”
Section: Simulation Of Tissue Growth On Scaffold In 3dmentioning
confidence: 99%